Religion, gender, and industry : exploring church and Methodism in a local setting - Hammond, Geordan; Forsaith, Peter S.; Hindmarsh, D. Bruce (Cambridge [UK] : James Clarke & Co., 2011)
A collection of essays that aim to consider broad questions of the role of religion in late eighteenth- and early nineteenth-century Britain by studying a single geographical area. Coalbrookdale in the parish of Madeley, Shropshire is seen as the ""birthplace of the industrial revolution"" while remaining one of the last examples of a Methodist parish in England. These works engage with a variety of areas of study: Methodism's roots and growth in relation to the Church of England, religion and gender in eighteenth century Britain, and religion and the emergence of an industrial society, and do.
Bishop Asbury's Indebtedness to FletcherBishop Asbury and His Preachers Affirmed PentecostalPerfection; The Prevalence of the Fletchers' Pentecostal Nomenclature in Early American Methodism; Conclusion; 13. The Long Fletcher Incumbency; Contributors; Back cover.
Essays originally presented at a conference held June 16-18, 2009 at the Telford (Priorslee) campus of the University of Wolverhampton with some sessions at Madeley and Ironbridge.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Fletcher, John, -- 1729-1785 -- Congresses; Fletcher, John, -- 1729-1785.; Methodism -- History -- 18th century -- Congresses; Methodism -- History -- 19th century -- Congresses; Methodism -- Doctrines; Madeley (Shropshire, England); RELIGION -- Christianity -- Methodist; Methodism; Methodism -- Doctrines; England -- Madeley (Shropshire); HISTORY / Europe / Great Britain; 1700-1899; Electronic books; Conference papers and proceedings; History